Swine model in cardiopulmonary resuscitation research - XANTHOS (Θ. ΞΑΝΘΟΣ), Th. (Journal of the Hellenic Veterinary Medical Society, 2017)
Cardiac Arrest (CA) constitutes a real medical emergency. Various experimental models have been developed in order to test experimental treatments. Animal models that have been used in CA research are rodents, rabbits, cats and dogs, primates and swine. Among these, swine are used more often. The reason behind this choice is mostly its close resemblance to the human cardiac anatomy and physiology. Various haemodynamic variables have been investigated as predictors of the return of spontaneous circulation (ROSC). Coronary Perfusion Pressure (CPP) is the only proven predictor for ROSC. CPP, which is responsible for myocardial perfusion, greatly augments during chest compressions. ROSC and therefore survival after CA has been associated with CCP values greater than 15 mmHg for humans and 25 mmHg for animals. For the experimental induction of CA various electric sources have been used. All these experimental devices could be potentially dangerous for researchers, even though, no incidence of electrocution has been reported in the international literature. The ordinary cadmium battery appears to be safer and is an extremely effective way of inducing cardiac arrest.